2010
DOI: 10.1124/dmd.109.030700
|View full text |Cite
|
Sign up to set email alerts
|

Role of P-Glycoprotein in the Disposition of Macrocyclic Lactones: A Comparison between Ivermectin, Eprinomectin, and Moxidectin in Mice

Abstract: ABSTRACT:Macrocyclic lactones (MLs) are lipophilic anthelmintics and substrates for P-glycoprotein (P-gp), an ATP-binding cassette transporter involved in drug efflux out of both host and parasites. To evaluate the contribution of P-gp to the in vivo kinetic disposition of MLs, the plasma kinetics, brain concentration, and intestinal excretion of three structurally different MLs (ivermectin, eprinomectin, and moxidectin) were compared in wild-type and P-gpdeficient [mdr1ab(؊/؊)] mice. Each drug (0.2 mg/kg) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 39 publications
6
59
0
Order By: Relevance
“…Cárcamo et al [36] showed that exposure of rainbow trouts to pharmacological EMB concentrations altered the transcriptional responses of xenobiotic biotransformation proteins and extrusion transporters. EMB increases CYP3A expression in kidney and intestine samples and it is wellknown that CYP3A enzymes participate strongly in drug interactions [37,38]. Probably, the lipophilic nature of EMB and its non-biotransformation may lead to its accumulation in the plasma and produce changes in many functions including renal, nerve and hepatic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Cárcamo et al [36] showed that exposure of rainbow trouts to pharmacological EMB concentrations altered the transcriptional responses of xenobiotic biotransformation proteins and extrusion transporters. EMB increases CYP3A expression in kidney and intestine samples and it is wellknown that CYP3A enzymes participate strongly in drug interactions [37,38]. Probably, the lipophilic nature of EMB and its non-biotransformation may lead to its accumulation in the plasma and produce changes in many functions including renal, nerve and hepatic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of brain tissue ivermectin concentrations in ivermectin-sensitive collies (Pulliam et al, 1985) supports a link between P-gp function and the CNS distribution of ivermectin. The CNS disposition of ivermectin and related macrocyclic lactones has also been linked to P-gp function in rodents (Schinkel et al, 1994;Kwei et al, 1999;Kiki-Mvouaka et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As we do not know the fine mechanism of ivermectin inhibition of this enzyme, albeit we reported some details in a previous work (Pimenta et al 2010), it could be argued that ivermectin should penetrate the membrane to interact with some putative intracellular locus of the transmembrane ATPases (Na + ,K + -ATPase and H + ,K + -ATPase). Note that ivermectin is very lipophilic (Log P of 3.217, 4.8, and 5.31 have been reported by Camargo et al 2010;Kiki-Mvouaka et al 2010 andBaynes 2009, respectively), so that it can easily penetrate the plasma membrane and reach the internal loops of these enzymes. It could also penetrate the cell and reach the SERCA, as occurs with thapsigargin, a lipophylic sequiterpene lactone that specifically inhibits this Ca 2+ -ATPase located in the sarco-endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 83%